Development of Engine Fire Protection System for Vehicle - Mohd Fauzi, Ahmad Hariz Danial; Mohammad Faiz Liew Bin Abdullah, (Evolution in Electrical and Electronic Engineering, 2024)
Engine fires in vehicles pose significant hazards to passengers and the environment, necessitating the development of an engine fire suppression system to enhance vehicle safety. This study aims to propose a technique for detecting and suppressing engine fires at an early stage and validate its functionality. The research objectives include designing a system consisting of a Fire Detection Unit (FDU) and a Fire Suppression Unit (FSU) and evaluating its effectiveness. The materials used for the study included IR flame sensors, a temperature sensor, and a CO2 fire suppression system. Standard procedures were followed in conducting experimental trials using a cubic test rig simulating the engine compartment. Key findings from the analysis of the designed system indicate that the FDU's flame sensors trigger a warning when the analog output falls below the threshold of 100, while the temperature sensor triggers a warning above 50°C. The FSU exhibited reliable functionality, with consistent extinguishing times ranging from 4.91s to 5.42s. Data analysis confirms the system's accuracy, with precision values ranging from 0.9499 to 0.9963. In summary, this study successfully developed an engine fire suppression system and demonstrated its effectiveness in detecting and suppressing engine fires. The findings suggest that the proposed technique can significantly contribute to enhancing vehicle safety. Future work may involve further optimizing the system design such as addition of CO2 gas sensor, transitioning from analog CO2 regulator to digital CO2 regulator and adding a subsystem to ease maintenance work.